Family Resilience Literacy (Case Study of P2K2 Activities) - Yusiyaka, Rahmi Alendra; Safitri, Ani; Mujahidin, Endin (Universitas Negeri Padang, 2020)
This study aims to provide an overview of family resilience literacy activities through P2K2 activities in the family hope program in the city of Bogor, a case study in Tanah Sareal sub-district with a total number of PKH participants as many as 4890 heads of families, spread over 11 (eleven) villages, divided into 131 groups. assistance in each village according to the conditions of each facilitator and assisted area. The research method used in this research is descriptive qualitative with a case study approach. The results of the study illustrate how family resilience literacy activities through group meetings called Family Development Sessions or better known as Family Resilience Enhancement Meetings, which will be abbreviated as P2K2.